2019
DOI: 10.29328/journal.cjog.1001039
|View full text |Cite
|
Sign up to set email alerts
|

Snake envenomation during pregnancy

Abstract: Background: We report our experience with management and treatment of pregnant women who were admitted at our institution for snake envenomation. Methods: We reviewed the charts and recorded the management, treatment, and outcome of 51 pregnant women admitted to our high-risk obstetric service with a diagnosis of snakebite. Results: One patient experienced spontaneous abortion, 2 had intrauterine fetal death due to placental abruption, 2 delivered malformed babies, 1 had premature birth of twins with low birth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In addition, envenomation during pregnancy is associated with adverse maternal and foetal outcomes [ 4 ]. The coagulating agent in the toxin can reach the decidua-placental cleavage zone and may start a dissociation leading to placental abruption [ 8 ]. Similarly, placental abruption was suspected in our case as the patients developed abdominal pain and heavy vaginal bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, envenomation during pregnancy is associated with adverse maternal and foetal outcomes [ 4 ]. The coagulating agent in the toxin can reach the decidua-placental cleavage zone and may start a dissociation leading to placental abruption [ 8 ]. Similarly, placental abruption was suspected in our case as the patients developed abdominal pain and heavy vaginal bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Foetal loss is more likely to occur early in the gestation period [ 21 , 44 ]. Abruptio placenta, especially in haemotoxic SBE, is the commonest cause of foetal loss [ 45 ]. Interestingly, the Brazilian study [ 21 ] showed no difference in severity or case fatality between pregnant and non-pregnant women of childbearing age.…”
Section: Pregnancymentioning
confidence: 99%
“…One review in 2010 reported a case fatality rate of 4.2% and 19.2% in pregnant women and neonates, respectively [ 22 ]. Mechanisms proposed to explain foetal deaths included anoxia secondary to maternal shock, abruptio placenta, venom-induced premature uterine contractions, and a direct venom effect on the foetus [ 45 ].…”
Section: Pregnancymentioning
confidence: 99%